Image processing algorithms for dynamic vision sensors - Wang, Lun (Nanyang Technological University, 2023)
This study presents a comprehensive examination of the DAVIS346 camera data, with the goal of advancing our understanding and application of this dynamic vision sensor. The research encompasses the entire lifecycle of the camera's deployment — from meticulous assembly, calibration, and testing procedures to the development of a sophisticated drone detection algorithm. Through an iterative process of design and refinement, the study has successfully demonstrated the camera's exceptional capabilities in capturing and processing high-temporal-resolution data.